Longitudinal Associations of Modifiable Lifestyle Factors With Positive Depression-Screen Over 2.5-Years in an International Cohort of People Living With Multiple Sclerosis - Taylor, Keryn L.; Simpson, Steve; Jelinek, George A.; Neate, Sandra L.; De Livera, Alysha M.; Brown, Chelsea R.; O'Kearney, Emily; Marck, Claudia H.; Weiland, Tracey J. (Frontiers in Psychiatry, 2018)
Background: Depression is common and has the most significant impact on quality of life for many people with multiple sclerosis (MS). A preventive management approach via modification of lifestyle risk factors holds potential benefits. We examined the relationship of modifiable lifestyle factors and depression risk and the change in depression over 2.5 years. Methods: Sample recruited using online platforms. 2,224 (88.9%) at baseline and 1,309 (93.4%) at 2.5 year follow up completed the necessary survey data. Survey data included depression risk, measured by the Patient Health Questionnaire-2 at baseline and Patient Health Questionnaire-9 at 2.5-year follow-up. Multivariable regression models assessed the relationships between lifestyle factors and depression risk, adjusted for sex, age, fatigue, disability, antidepressant medication use, and baseline depression score, as appropriate. Results: The prevalence of depression risk at 2.5-year follow-up in this cohort was 14.5% using the PHQ-2 and 21.7% using the PHQ-9. Moderate alcohol intake, being a non-smoker, diet quality, no meat or dairy intake, vitamin D supplementation, omega 3 supplements, regular exercise, and meditation at baseline were associated with lower frequencies of positive depression-screen 2.5 years later. Moderate alcohol intake was associated with greater likelihood of becoming depression-free and a lower likelihood of becoming depressed at 2.5-year follow-up. Meditating at least once a week was associated with a decreased change in losing depression risk, against our expectation. After adjusting for potential confounders, smoking, diet, physical activity, and vitamin D and omega-3 supplementation were not associated with a change in risk for depression. Conclusion: In a large prospective cohort study of people with MS and depression, in line with the emerging treatment paradigm of early intervention, these results suggest a role for some lifestyle factors in depression risk. Further studies should endeavour to explore the impact of positive lifestyle change and improving depression in people living with MS.